Analisis Proses Pembelajaran Daring Masa Pandemi Covid-19 Di SD N 2 Karangharjo Grobogan - Niken Niken Suprapti; Ika Oktavianti; Muhammad Noor Ahsin (WASIS : Jurnal Ilmiah Pendidikan, 2022)
This study aims to describe the process and constraints of online learning during the Covid-19 pandemic in class V SD N 2 Karangharjo.This research uses descriptive qualitative research. This research was conducted at SD N 2 Karangharjo. The data in this study were obtained using non-test techniques consisting of interviews, observation and documentation. Research instruments include interview sheets, and observation sheets. Data analysis techniques used interactive techniques consisting of data collection, data reduction, data presentation, and conclusions.The results of this study show that the online learning process is carried out at SD N 2 Karangharjo through the whatsapp application where all the learning processes in the form of delivering materials, assignments, and collecting assignments are all through the whatsapp application and the implementation is also carried out in a bolster (mobile teacher). These efforts are quite effective because in improving the quality of learning with these efforts students are more enthusiastic about learning than independent learning at home, students can ask questions directly about materials that are not understood, and children can interact directly between educators and students.